Peran Orang Tua Dalam Pembentukan Karakter Anak Cerebral Palsy di Yayasan Rumah Gadang Padang - Tayuni, Cherli Dwi; Nurhastuti, Nurhastuti (Jurnal Penelitian Pendidikan Khusus, 2022)
The background of this study is the role of parents in the development of the cerebral palsy child. In this character creation the role of parents is essential. The purpose of this study is to understand the role of parents to develop character to cerebral palsy children. This research method is a quantitative using data collection techniques through distribution of angkettes to 22 parents as a research subject. The data collected later in athletically USES a presentation technique that would later be thoroughly described. According to the results of this study, the new general term suggests that the parents have been applying general information transfer to cerebral palsy. Parental role is listed as a educator with a result of 54%, but a parent's role as a 32% facilitator, a parent's role as a companion of 32% and a motivational parent with 42% recorded poorly.